2014
DOI: 10.3389/fphys.2014.00098
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng ginsenoside pharmacology in the nervous system: involvement in the regulation of ion channels and receptors

Abstract: Ginseng, the root of Panax ginseng C.A. Meyer, is one of the oldest traditional medicines and is thought to be a tonic. It has been claimed that ginseng may improve vitality and health. Recent studies have advanced ginseng pharmacology and shown that ginseng has various pharmacological effects in the nervous system. Ginsenosides, steroid glycosides extracted from ginseng, were one of the first class of biologically active plant glycosides identified. The diverse pharmacological effects of ginsenosides have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 87 publications
0
68
1
Order By: Relevance
“…5a). Moreover, there was no difference in the discrimination ratio (F [3,34] = 0.775, p = 0.516; Fig. 5b).…”
Section: Oral Administration Of Gintonin Alleviates Object Location Mmentioning
confidence: 99%
See 2 more Smart Citations
“…5a). Moreover, there was no difference in the discrimination ratio (F [3,34] = 0.775, p = 0.516; Fig. 5b).…”
Section: Oral Administration Of Gintonin Alleviates Object Location Mmentioning
confidence: 99%
“…The ginseng extract contains several bioactive ingredients, such as acidic polysaccharides, which are known to stimulate the immune system; ginsenoside, one of the saponins produced by this plant, exhibits diverse but nonspecific biological effects [3]. However, these ginseng ingredients do not fully account for the molecular mechanism(s) responsible for the ginseng extract-mediated beneficial effects on brain functions and anti-brain aging because they do not target a specific membrane protein [3]. Moreover, recent studies have demonstrated that ginseng extract includes a novel component called gintonin, which is a non-acidic polysaccharide and a non-saponin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the effects of ginsenosides on glutamatergic transmission have been found, which could regulate presynaptic neurotransmitter release and postsynaptic receptor activity [9]. Duan and Nicholson [10] reported that ginsenoside Rh2 inhibited Na + channel-dependent amino acid neurotransmitter release from presynaptic nerve terminals.…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenosides, the major active components from stems and leaves of Panax ginseng, have been reported to show various protective effects on ischemic brain injury [3-5]. To search for the neuroprotective agents, we had compared the neuroprotective effects of 9 individual ginsenosides (Rb1, Rb3, Rd, Re, Rg1, Rg2, Rh1, Rh2, and F11) in hippocampal slices, and found that Rb1, Rb3, Rg1, Rh2, and F11 could protect neurons among them [6].…”
Section: Introductionmentioning
confidence: 99%